2019
DOI: 10.3390/ma12152361
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids-Functionalized Zeolitic Imidazolate Framework for Carbon Dioxide Adsorption

Abstract: Ionic-liquid-functionalized zeolitic imidazolate frameworks (ZIF) were synthesized using the co-ligands of 2-methylimidazole and amine-functionalized ionic liquid during the formation process of frameworks. The resulting ionic-liquid-modified ZIF had a specific surface area of 1707 m2·g−1 with an average pore size of about 1.53 nm. Benefiting from the large surface area and the high solubility of carbon dioxide in ionic-liquid moieties, the synthesized materials exhibited a carbon dioxide adsorption capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The peaks at 26. [39][40][41]. This indicates the complete conversion of pristine ZIF-67 to nanocarbon structures and the transformation of the ZIF-67 framework during carbonization.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The peaks at 26. [39][40][41]. This indicates the complete conversion of pristine ZIF-67 to nanocarbon structures and the transformation of the ZIF-67 framework during carbonization.…”
Section: Resultsmentioning
confidence: 85%
“…At the same time, the broad (002) peak and (111), (200), and (220) peaks were generated. The peaks at 26.2°, 44.3°, 51.6°, and 75.9° of 2θ represent the carbonaceous materials ((002)), Co and CoO ((111), (200), and (220)), respectively [39][40][41]. This indicates the complete conversion of pristine ZIF-67 to nanocarbon structures and the transformation of the ZIF-67 framework during carbonization.…”
Section: Resultsmentioning
confidence: 95%
“…It can be seen that N atoms in the composite material have four different bonding states with the binding energy centered at 398.28, 398.99, 400.09, and 401.03 eV. It has been reported that the peaks centered at 400.09 and 401.03 eV corresponded to the C-N and C=N bonding on the imidazole rings of ionic liquid moieties [28]. The peaks at 398.28 and 398.99 eV can be therefore assigned to amino groups.…”
Section: Resultsmentioning
confidence: 98%
“…Particularly, amine-functionalized porous materials with a large surface area have been extensively investigated, and literature results have revealed that these materials are promising solid sorbents for CO 2 adsorption [12][13][14][15][16][17][18][19][20]. Of the solid porous materials applied for CO 2 adsorption, metal organic frameworks (MOFs) have attracted great attention due to their large surface area and the easy process for surface modification as pioneered by Yaghi [21][22][23][24][25][26][27][28] and well described in recently published topic reviews [29,30]. Among the developed MOF materials, Cu 3 (BTC) 2 synthesized from Cu 2+ and 1-Vinylimidazole (1-VIm, purity of 99%), 2-bromoethanamine hydrobromide (98%), and 2,2-azobisisobutyronitrile (AIBN) were purchased from Alfa Aesar (MA, US).…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, ZIF-67 has not been used to detect H 2 S gas [ 13 , 27 , 28 ] but rather other VOC gases [ 27 , 28 , 29 , 30 , 31 , 32 ] and inorganic gases [ 33 , 34 , 35 ]. It has also been used in water purification [ 15 , 36 , 37 , 38 , 39 ] CO 2 detection and separation [ 14 , 40 , 41 , 42 , 43 ], organic dyes [ 19 , 36 , 44 ], electrochemical sensors [ 16 , 45 , 46 ], and energy applications [ 23 , 47 , 48 ]. To the best of our knowledge, ZIF-67 has not been reported in combination with CS for H 2 S gas detection applications.…”
Section: Introductionmentioning
confidence: 99%